2015
DOI: 10.1089/jir.2014.0156
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of Cytokine-Induced Killer Cells and Cyclosporine A for the Treatment of Aplastic Anemia in a Mouse Model

Abstract: In this study, we investigated the combined use of cytokine-induced killer (CIK) cells and cyclosporine A (CsA) to treat a mouse model of aplastic anemia (AA). CIK cells were cultured and injected alone or in combination with CsA into mice that had previously been induced into AA by busulfan and mouse interferon-γ (IFN-γ). The CIK cell-treated group had a survival rate of 55%, which was similar to the 60% survival rate observed in the CsA-treated group. The combination group showed a survival rate as high as 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…Regarding cytokine/chemokine secretion, we observed no significant differences between CIK cells with and without MPA treatment expect for a significant reduction in TNFα secretion. These results are in accordance with Liu et al [ 36 ] who published promising results combining CIK cell therapy with CsA treatment also describing the secretion of various cytokines including IL-2 and IL-8. In contrast, Brehm et al [ 9 ] and Nagy et al [ 37 ] reported a significant reduction in the secretion of IFNγ, IL-6 and other cytokines by NK cells upon MPA treatment, but here immune cells were co-incubated with MPA already during cultivation time.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding cytokine/chemokine secretion, we observed no significant differences between CIK cells with and without MPA treatment expect for a significant reduction in TNFα secretion. These results are in accordance with Liu et al [ 36 ] who published promising results combining CIK cell therapy with CsA treatment also describing the secretion of various cytokines including IL-2 and IL-8. In contrast, Brehm et al [ 9 ] and Nagy et al [ 37 ] reported a significant reduction in the secretion of IFNγ, IL-6 and other cytokines by NK cells upon MPA treatment, but here immune cells were co-incubated with MPA already during cultivation time.…”
Section: Discussionsupporting
confidence: 92%
“…It is released from mitochondria and translocates to nuclei, followed by the induction of chromatin condensation and DNA degradation during cell apoptosis ( 37 ). To date, previous studies have indicated that CsA has a therapeutic effect on a number of diseases through various pathways, including reducing the proportion of CD4(+) T cells and the expression level of interferon-i for the treatment of aplastic anemia ( 38 ). Guan et al ( 39 ) demonstrated that CsA has a protective effect in improving mitochondrial function through inhibiting mitofusin proteins, which are located on the outside of mitochondrial membranes and regulate mitochondrial fusion.…”
Section: Discussionmentioning
confidence: 99%